Appraising Trends in Residential Property Investment Returns Relative to Infrastructure Conditions in Ilorin, Nigeria - Adeogun, Sunday Adekunle; Abass, Sule Iyanda; Amuda-Yusuf, Ganiyu (Journal of Technology Management and Business, 2020)
Infrastructure serves as an indicator to make real estate investment flourish, build the platform for the real estate investment market to thrive, and also to boost returns on property investment. Despite the availability of some infrastructure, the property investment market still plagued with less expected returns as a result of non-functionality of neighbourhood infrastructure. The study focused on the appraisal of the trends in residential property investment returns between year 2009 to 2018, relative to infrastructure condition in the study area. Data were obtained from practising real estate firms and residents of selected neighbourhoods using a structured questionnaire. The study adopted a simple random sampling technique. Out of 2,228 questionnaires administered in the selected neighborhoods, in Ilorin, 664 were returned and valid for the analysis. Descriptive mean method of data analysis was employed, coefficient of variation and spearman’s rank-order correlation model was adopted to compare the property investment return in the selected areas of Ilorin and to determine the infrastructure index with benchmark for the minimum acceptable standard condition. Also, Kendall coefficient of concordance was also used to test the relationship among the ranked factors. The result shows that Sabo-Oke and Fate property market of Ilorin performed better than Adewole Housing Estate and GRA (Government Reservation Area) based onrisk- return ratio analysis, of which Sabo-Oke and Fate revealed the most consistent property market returns while GRA and Adewole Housing Estate residential market showed high level market volatility due to risky nature of the market. Sabo-Oke and Fate markets showed a stable market at minimum risk ranges between 8%-36%. The infrastructure condition indices in GRA and Adewole Housing Estate is higher than ideal condition index (Benchmark), ranges between 82%-92% and 81%-94% when compared with the average international standard at 60%, while infrastructure conditions in Sabo-Oke and Fate found a bit below the average international standard condition. The study also found that the performance of residential property investment is magnificent in the area where there is a frequent market transaction with good and functional infrastructure, as it is discovered across the selected neighbourhoods in Ilorin. The study concluded that infrastructure has a weighty influence on residential property investment returns relative to functional infrastructure and that, residential property market performance hinges on functional infrastructure and it must be given extreme consideration when making a property investment decision.